2006
DOI: 10.1007/s10706-006-9112-5
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of model footing on pond ash

Abstract: This paper focuses on the effective utilization of pond ash, as foundation medium. A series of laboratory model tests have been carried out using square, rectangular and strip footings on pond ash. The effects of dry density, degree of saturation of pond ash, size and shape of footing on ultimate bearing capacity of shallow foundations are presented in this paper. Local shear failure of a square footing on pond ash at 37% moisture content (optimum moisture content) is observed up to the values of dry density 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Therefore it is quite clear that BCR increases with the increase in the footing width (B) and this trend is unaffected by the value of extent ratio (X). Although results reported earlier in the literature [15,16] cites similar trend for unreinforced cases, and this trend remained unchanged even when sand subgrades were reinforced with vertical reinforcements beyond the footing base.…”
Section: Effect Of Width Of Footing (B)supporting
confidence: 78%
“…Therefore it is quite clear that BCR increases with the increase in the footing width (B) and this trend is unaffected by the value of extent ratio (X). Although results reported earlier in the literature [15,16] cites similar trend for unreinforced cases, and this trend remained unchanged even when sand subgrades were reinforced with vertical reinforcements beyond the footing base.…”
Section: Effect Of Width Of Footing (B)supporting
confidence: 78%
“…Bera Ashis Kumar (2013) reported that with the increase in pond ash content (0%e30%) of the pond ash mixed soil, the value of unconfined compression strength decreases significantly, whereas, with addition of pond ash (above 40%) the changes of unconfined compression strength of pond ash mixed soil is not appreciable. Bera et al (2007) reported that with the increase in compactive efforts, MDD increases and at the same time OMC decreases. Chand and Subbarao (2007) presented the effects of lime stabilization on the strength and durability aspects of a class F pond ash, with a lime constituent as low as 1.12%, are reported.…”
Section: Pond Ash/rice Husk Ash Stabilizationmentioning
confidence: 99%
“…California bearing ratio of pond ash has been found to improve with the addition of lime [24]. An experimental study has shown that increase in compactive efforts lead to an increase in MDD and simultaneous decrease in OMC [25]. It has been concluded that the cement stabilized and fiber reinforced clay mixed with optimum percentage of rice husk ash and pond ash can be an effectively used as geotechnical fill materials [26].…”
Section: Introductionmentioning
confidence: 99%